Civic budget and its role in the process of urban reconstruction - a case study of the city of Lodz - Ślebocka, Magdalena; Kilanowski, Artur (Journal of Finance and Financial Law, 2023)
The purpose of the article/hypothesis: The aim of the article is to assess the role and importance of the civic budget in a broader processes of reconstruction of the degraded urban fabric in the period 2016–2023. The article poses a research hypothesis that the civic budget, as an advanced form of social participation not limited to information or public consultation, is a tool supporting the implementation of revitalization processes undertaken in the city. The research questions were helpful in verifying the proposed hypothesis: 1) Does the civic budget support revitalization processes? 2) What types of projects submitted as part of the civic budget are included in revitalization measures? 3) How is the tool that the civic budget is in revitalization perceived by stakeholders and initiators of these processes? Methodology: The research involved a literature review and an analysis of numerical data and information on revitalization projects that can be found in the civic budget of Lodz. The study also used an original survey questionnaire conducted among the residents. Results of the research: It was found that the civic budget in Lodz contributed to the implementation of a number of revitalization projects. The high civic awareness of the residents and their knowledge of the needs of their surroundings make it possible to implement these projects in areas where the condition of the urban fabric is critical. Thanks to the civic budget, the city’s residents have had and continue to have an opportunity to make changes in their immediate environment. They can realize the most important investments from the point of view of local needs.